2003
DOI: 10.1007/s10038-003-0038-y
|View full text |Cite
|
Sign up to set email alerts
|

A mutation analysis of the BRCA1 gene in 140 families from southeast France with a history of breast and/or ovarian cancer

Abstract: A mutation analysis of the BRCA1 gene in 140 French families with a history of breast cancer or breastovarian cancer revealed several deleterious germline mutations, as well as rare sequence variants. The 19 genetics variants were of 15 different types, two of which had not been reported in the Breast cancer Information Core (BIC) database. Five distinct truncating mutations, leading to putative nonfunctional proteins, were identified out of 140 index cases (3.5%). One novel nonsense mutation, C4491T, was repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Differences also existed in the composition of the two study groups, as the presence of large familial breast/ovarian cancer families with more than one first‐degree affected member who were analyzed for BRCA1 mutations was limited to 10 non‐related cases in the current study (16.1%, 95% CI: 8–27.7%). Similar frequencies have been reported in other southern European countries including France (12%) (9), Italy (9%) (10), and a cumulative study by Frank et al (9.2%) (11).…”
Section: Discussionsupporting
confidence: 87%
“…Differences also existed in the composition of the two study groups, as the presence of large familial breast/ovarian cancer families with more than one first‐degree affected member who were analyzed for BRCA1 mutations was limited to 10 non‐related cases in the current study (16.1%, 95% CI: 8–27.7%). Similar frequencies have been reported in other southern European countries including France (12%) (9), Italy (9%) (10), and a cumulative study by Frank et al (9.2%) (11).…”
Section: Discussionsupporting
confidence: 87%
“…It is estimated that around 5-10% of all breast and ovarian cancers are due to an inherited predisposition [20]. Most of the mentioned hereditary cases have been related to mutations within the BRCA1/2 genes.…”
Section: Genetic Polymorphisms Within the Brac1/2 Genesmentioning
confidence: 99%
“…Two BRCA1 missense mutations, T243C and A120G were reported to modify the initiation codon and have severe results on the function and structure of the BRCA1 protein product by altering the interaction of cysteine ligands. They also found that BRCA1 gene alteration was more common in families with breast-ovarian cancer history than breast cancer families alone [20]. In another study conducted in Chile, a sample of 64 high-risk ovarian and breast carcinoma families were screened for exon-intron boundaries of BRCA1/2 genes and germline mutations in the coding region using conformationsensitive gel electrophoresis and direct DNA sequencing techniques.…”
Section: Genetic Polymorphisms Within the Brac1/2 Genesmentioning
confidence: 99%
“…A considerable number of these VUS were found to interfere with the RNA splicing process. These VUS can produce new splicing transcripts or affect the ratio of naturally occurring alternative splicing transcripts of the BRCA1 gene (110,(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126).…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%